Cleavage of double-stranded RNA by RNase HI from a thermoacidophilic archaeon, Sulfolobus tokodaii 7 - Ohtani, Naoto (Oxford University Press, 2004)
ST0753, the orthologous gene of Type 1 RNase H found in a thermoacidophilic archaeon, Sulfolobus tokodaii, was analyzed. The recombinant ST0753 protein exhibited RNase H activity in both in vivo and in vitro assays. The protein expressed in an RNase H-deficient mutant Escherichia coli strain functioned to suppress the temperature-sensitive phenotype associated with the lack of RNase H. The in vitro characteristics of the gene's RNase H activity were similar to those of Halobacterium RNase HI, the first archaeal Type 1 RNase H to be characterized. Surprisingly, the S.tokodaii RNase HI cleaved not only the RNA strand of an RNA/DNA hybrid but also an RNA strand of an RNA/RNA duplex in the presence of Mn(2+) or Co(2+). The result of gel filtration column chromatography showed this double-stranded RNA-dependent RNase (dsRNase) activity was coincident with S.tokodaii RNase HI. A site-directed mutagenesis study of essential amino acids for RNase H activity indicated that this activity also affected dsRNase activity. A single amino acid replacement of Asp-125 by Asn resulted in loss of dsRNase activity but not RNase H activity, suggesting that amino acid residues required for dsRNase activity seemed slightly different from those of RNase H activity. Some reverse transcriptases from retroelements can cleave double-stranded RNA, and this activity requires the RNase H domain. Similarities in primary structure and biochemical characteristics between S.tokodaii RNase HI and reverse transcriptases imply that the S.tokodaii enzyme might be derived from the RNase H domain of reverse transcriptase.